Core fluorination enhances solubility and ambient stability of an IDTbased ntype semiconductor in transistor devices - Hodsden,T; Thorley,KJ; Panidi,J; Basu,A; Marsh,AV; Dai,H; White,AJP; Wang,C; Mitchell,W; Glöcklhofer,F; Anthopoulos,TD; Heeney,M (Advanced Functional Materials, 2020)
The synthesis of a novel fluorinated ntype small molecule based on an indacenodithiophene core is reported. Fluorination is found to have a significant impact on the physical properties, including a surprisingly dramatic improvement in solubility, in addition to effectively stabilizing the lowestunoccupied molecular orbital energy (−4.24 eV). Singlecrystal analysis and density functional theory calculations indicate the improved solubility can be attributed to backbone torsion resulting from the positioning of the fluorine group in close proximity to the strongly electronwithdrawing dicyanomethylene group. Organic thinfilm transistors made via blade coating display high electron mobility (up to 0.49 cm2 V−1 s−1) along with good retention of performance in ambient conditions.